Immune imbalance of regulatory T/type 2 helper cells in the pathogenesis of allergic rhinitis in children. Issue 1 (1st December 2015) - Sun, R; Tang, X-Y; Yang, Y
Abstract: Objectives: To determine the role of regulatory T/type 2 helper cell-mediated immune imbalance in the pathogenesis of allergic rhinitis and examine the association between clinical severity and regulatory T/type 2 helper cell-mediated immune imbalance. Methods: Levels of interleukins 4 and 5 and transforming growth factor β1, and expression of FOXP3 and GATA3 (which are functionally related to regulatory T and type 2 helper cells, respectively), were evaluated in 46 allergic rhinitis patients and 42 healthy subjects. Results: Compared to controls, allergic rhinitis patients showed significantly higher interleukin 4 and 5 levels, but lower transforming growth factor β1 levels. Furthermore, FOXP3 messenger RNA expression was lower in allergic rhinitis patients, while GATA3 messenger RNA and protein expression was significantly higher. Regulatory T/type 2 helper cell ratio was inversely correlated with clinical symptom scores. Conclusion: Regulatory T/type 2 helper cell immune imbalance may contribute to allergic rhinitis development. These findings provide a new insight into disease pathogenesis and potential therapeutic approaches.